Kepemimpinan Pendekatan Sifat Dalam Organisasi - M Fahri Nursalim; Agustin Pratiwi; Sanida Nisa Farasi; Mochammad Isa Anshori (CV. Aksara Global Akademia, 2023)
Most definitions of leadership reflect the assumption that leadership is concerned with the intentional process of a person exerting a strong influence over others. The purpose of this research is to know the importance of the trait approach in an organization. In this study, we define leadership according to individual perspective and the aspect of the symptom that attracts the most attention. The research method uses the method (Library research) the purpose of this study is to find out the importance of leadership theory.